"Historia literatury polskiej" pióra Czesława Miłosza - Piotrowska-Grot, Magdalena (Śląskie Studia Polonistyczne, 2014)
The author examines creative principles of writings on literary history by Czesław Miłosz. Historia literatury polskiej is a bridge between traditional thinking about history of literature and redefining this issue. His proposition mirrors the creator’s loose thinking about central and secondary issues and becomes in a way a post-modern textbook for foreigners. Miłosz’s method, also utilized in his books Mój wiek XX and Wyprawa w Dwudziestolecie is based on specific, individual solutions; however, in order to see them, one must analyze the writer’s historical and creative method – suspending the discourse between literacy and orality. The history of literature described by Miłosz is clearly not a finite, complete synthesis, but rather – as H.R. Jauss put it – a provocation towards further research.